2013
DOI: 10.1073/pnas.1213212110
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of type III phosphatidylinositol phosphate kinase in murine embryonic visceral endoderm and adult intestine

Abstract: The metabolism of membrane phosphoinositides is critical for a variety of cellular processes. 5)P 2 ] controls multiple steps of the intracellular membrane trafficking system in both yeast and mammalian cells. However, other than in neuronal tissues, little is known about the physiological functions of PtdIns(3,5)P 2 in mammals. Here, we provide genetic evidence that type III phosphatidylinositol phosphate kinase (PIPKIII), which produces PtdIns(3,5)P 2 , is essential for the functions of polarized epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 37 publications
3
67
0
Order By: Relevance
“…To determine whether PIKfyve is a regulator of synapse strength, we knocked-down PIKfyve in mouse hippocampal cultured neurons using lentiviral expression of PIKfyve-targeting shRNA and compared miniature excitatory postsynaptic currents (mEPSCs) of shRNA-expressing neurons with sham or nontargeting controls. One week postinfection, PIKfyve shRNA causes small vacuoles to appear, a phenotypic hallmark of reduced PI(3,5)P 2 levels (16,21,28,34,35). We found that the amplitude of mEPSCs in PIKfyve shRNA-transduced neurons is significantly higher than sham or nontargeting control neurons ( Fig.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…To determine whether PIKfyve is a regulator of synapse strength, we knocked-down PIKfyve in mouse hippocampal cultured neurons using lentiviral expression of PIKfyve-targeting shRNA and compared miniature excitatory postsynaptic currents (mEPSCs) of shRNA-expressing neurons with sham or nontargeting controls. One week postinfection, PIKfyve shRNA causes small vacuoles to appear, a phenotypic hallmark of reduced PI(3,5)P 2 levels (16,21,28,34,35). We found that the amplitude of mEPSCs in PIKfyve shRNA-transduced neurons is significantly higher than sham or nontargeting control neurons ( Fig.…”
Section: Resultsmentioning
confidence: 58%
“…The pools of PI3P that are converted to PI(3,5)P 2 may derive from the class III PI 3-kinase VPS34 (29) and/or the class II PI 3-kinase C2α (30). In vivo, depletion of PIKfyve affects both PI(3,5)P 2 and PI5P pools (10,21,24,28). Identification of PI(3,5)P 2 and PI5P protein effectors will likely reveal specific roles for each lipid.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During conversion to the late endosome, PtdIns3P receives a phosphate moiety via activity of phospholipid kinase PIPK(III), and becomes phosphatidylinositol 3,5-bis-phosphate (PtdIns3,5P2), which then recruits several proteins including Chmp5, which is required for forming the inwardly directed invagination of the late endosome membrane, and also essential for perigastrulation development in mice (Shim et al, 2006). Loss of PIPK(III) in mouse embryos results in formation of gigantic endosomes in cells, indicating that they are unable to transfer the limiting membranes toward inside, but rather accumulate massively, In addition, the mutant embryos are not able to complete gastrulation, indicating that the late endosome assembly is tightly coupled to embryogenesis (Takasuga et al, 2013).…”
Section: The Late Endosome and Lysosome: Termination Of The Receptor-mentioning
confidence: 99%
“…Therefore, defects in late endosome maturation may cause developmental phenotypes, as seen in mutation of PIPK(III) (Takasuga et al, 2013) or the rab7 small GTP binding protein (Kawamura et al, 2012). mVam2 is a subunit of the tethering complex functioning in the late endosomes (Brocker et al, 2012).…”
Section: The Late Endosome and Lysosome: Termination Of The Receptor-mentioning
confidence: 99%